Fault-tolerant Algebraic Interleaver Architecture for IDMA Systems in Harsh Environments - Kong, Byeong-Yong (Journal of semiconductor technology and science, 2025)
In this paper, a fault-tolerant algebraic interleaver architecture is presented for interleave division multiple access (IDMA) systems operating in harsh environments. Since the multiuser detection procedure is performed chipby-chip according to an interleaving pattern, it is of paramount importance to keep track of the current index at all times. To protect the interleaving index in a register from soft errors, an encoder and a decoder associated with an error-correcting code are added. Moreover, to mitigate the latency overhead of such an architecture, the encoder is merged with an essential logic that precomputes the next index. As a result, the proposed interleaver tolerates soft errors while suppressing the latency overhead. KCI Citation Count: 0